Interactive organic chemistry - Vining, William J.; Rotello, Vincent M.; Bak, David A. (United States of America : Thomson, 2001)
The interactive organic chemistry CD-Rom is dual platform (runs in both Windows and Macintosh operating systems) stand-alone component shrinkrapped with a workbook .
Table of contents Thomson Learning Organic Chemistry CD-Rom Mechanisms Multistep Synthesis Numenclature Reactivity explorer Spectroscopy Supporting concepts
Keywords: ORGANIC CHEMISTRY; QUÍMICA ORGANICA